1996
DOI: 10.1073/pnas.93.7.3074
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mRNA splicing in plants: characterization of Ser/Arg splicing factors.

Abstract: The fact that animal introns are not spliced out in plants suggests that (1,2).Among the few well-characterized metazoan splicing factors are the proteins SF2/ASF, which is involved in selection of the 5' splice site, and U2AF, which stimulates the interaction of U2 snRNP with the branch point region. It has been shown that these and other splicing factors contain a similar structural motif, termed the RS domain (3). These proteins are phosphorylated in vivo and share a serine phosphoepitope recognized by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 49 publications
1
69
0
Order By: Relevance
“…Candidate intron recognition factors include two proteins from Nicotiana plumbaginifolia with poly(U) af®nity (Gniadkowski et al, 1996). Members of the serinearginine-rich protein family of splicing factors have also been identi®ed in plants (Lazar et al, 1995;Lopato et al, 1996), although their exact roles in pre-mRNA splicing are unclear presently. Our analysis of experimental studies of splicing of animal genes in plants suggests that the plant-speci®c compositional contrast between exons and introns is suf®cient to explain success and failure of splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate intron recognition factors include two proteins from Nicotiana plumbaginifolia with poly(U) af®nity (Gniadkowski et al, 1996). Members of the serinearginine-rich protein family of splicing factors have also been identi®ed in plants (Lazar et al, 1995;Lopato et al, 1996), although their exact roles in pre-mRNA splicing are unclear presently. Our analysis of experimental studies of splicing of animal genes in plants suggests that the plant-speci®c compositional contrast between exons and introns is suf®cient to explain success and failure of splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblot analysis with mAb104 suggested previously that the complexity of the SR protein family is higher in animals than in plants (Lopato et al 1996a), as several higher molecular mass proteins have been identified in SR preparations from mammals but not from those in plants. The existence of two SF2/ASF-like factors in Arabidopsis may compensate for the absence of orthologs of other members of the SR protein family.…”
Section: Two Sf2/asf-like Splicing Factors In Arabidopsismentioning
confidence: 99%
“…The proteins were detected with the monoclonal antibody mAb104, specific for a shared phosphoepitope in all SR proteins, and with a monoclonal antibody specific for the human SF2/ASF splicing factor (Lopato et al 1996a). A protein of ∼50 kD from the carrot SR preparation, which was recognized by both antibodies, was isolated and partially sequenced.…”
Section: Isolation and Sequencing Of Genomic And Cdna Clones Of Atsrp30mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Ser/Arg-rich (SR) proteins comprise a conserved family of premRNA splicing factors which function in splice site recognition and the spliceosome assembly, and that are required for constitutive and some aspects of alternative splicing. 46,47 At least 2 SR proteins, namely SRZ-21 and SRZ-22, interact with the plant U1 snRNP 70K protein. 48 Analyses of the biogenesis of miRNAs derived from intron-containing MIR genes in Arabidopsis null mutants of selected SR genes showed that the levels of mature miR161, miR163, and miR171 were decreased in 3 out of 4 mutants tested (rs31-1, rs2z33-1, and sr34-1).…”
mentioning
confidence: 99%